Effect of a simple intervention on hand hygiene related diseases in preschools in South Africa: research protocol for an intervention study - Nisha Naicker; Samantha Louise Lange; Tobias George Barnard (BMJ Open)
Introduction Hand hygiene (HH) related illnesses such as diarrhoea and respiratory diseases, contribute to the burden of disease and are included in the top five causes of mortality in children under 5 years in South Africa. Children attending preschools are more susceptible to these infections due to the higher number of children in preschools. HH interventions have shown to reduce HH-related diseases by improving HH practices. In South Africa, there are no documented HH interventions or studies in children under 5 years. The purpose of the study is to determine whether an HH intervention can reduce HH-related diseases among 4–5-year-old preschool children and to improve HH practices in these children, their caregivers and their parents.Methodology and analysis This is a protocol for a controlled intervention study to be conducted at preschools in Kempton Park, City of Ekurhuleni, Gauteng, South Africa. Preschools will be randomly distributed into control and experimental groups (n=70). The intervention includes interactive simulation learning, educational emails and education and poster reminders obtained from the WHO and the Global Handwashing Day website. Data collection, including the intervention, will take place during the calendar year as this coincides with the school year. Data will be analysed both preintervention and postintervention in the experimental group as well as between the experimental and control group. Data collected by means of questionnaires, observations, disease registers, hygiene inspections, semi-structured interviews and hand swabs will be analysed to determine these outcomes.Ethics and dissemination Permission has been obtained from the University of Johannesburg Ethics Committee and Ministerial Consent for Non-Therapeutic Research on Minors from the Department of Health National Ethics Research Council. Permissions for use of copyright protected materials has been obtained. Results of the study will be disseminated through peer-reviewed publications, and feedback within relevant structures through conference proceedings.